ANALISIS HADITS TARBAWI TENTANG ILMU DAN KEUTAMAAN ORANG BERILMU DALAM PERSPEKTIF PENDIDIKAN ISLAM: Hadis Tarbawi; Ilmu Pengetahuan; Keutamaan Orang Berilmu; Pendidikan Karakter - Iis Sumarni, Nuraida Rahmah Wati Dewi; Wahyudi, Hafidz Akbar; Hidayat, Arief; Ramdhani, Muhammad Rendi (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2025)
Islamic education focuses not only on intelligence but also on character development through the integration of spiritual and ethical values. The Hadith, the second source of Islamic teachings after the Qur'an, contains numerous messages related to character education, particularly regarding the importance of knowledge and the position of those who possess knowledge. This study aims to examine the contribution of hadiths on knowledge and the virtues of those who possess knowledge to character formation in Islamic education. The method applied in this study is descriptive qualitative with a library research approach, through an analysis of the content and themes of hadith works and Islamic educational sources. The results show that these hadiths contain important character values such as sincerity, responsibility, humility, and a passion for seeking knowledge. Those who possess knowledge are depicted as superior to ordinary worshippers because their knowledge provides broad benefits to society and is a legacy of the prophets. The conclusion of this study shows that integrating hadith values into the education system is crucial for developing students who are not only intellectually intelligent but also instill the values of tarbawi (Islamic education) comprehensively. Keywords: Tarbawi Hadith, Knowledge, Virtue of the Learned, Character Education